Neologisms as a Driving Force for the Development of Lexis in the German Language - Kruashvili, Irina (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
Quick scientific and technological progress has caused major changes in the lexical stores of languages. The aim of the present article is to find out, what changes occur in the German lexicon against the background of the scientific or technological achievements, how the last events are reflected in neologisms, how neologisms are born and what sorts of neologisms are abundant in the modern German language. We use several methods for the research, namely, descriptive method, method of immediate constituents and method of substitution. The article analyses neologisms of the modern German language according to the way of nascence and semantic parameters. New words are discussed which have arisen during the corona pandemic. Due to the research there has been elucidated that in the newest tendencies of the modern German language there is clearly revealed the influence of neologisms. The greatest share among the mentioned neologisms is made by nouns that denote objects of phenomena important for the society. Composite models are very productive, namely, determinative composites consisting of two immediate constituents. Next in frequency come composites with three members. There also occur composites consisting of four immediate constituents. Word building constructions, where one or two direct constituents are represented by English words, are frequent, too, and certain neologisms are borrowed from the English as completely ready-made words. In terms of frequency, the next place is occupied by adjectives, and verbs are the ones that occur least frequently. In terms of semantics, there occur the different word-building meanings.